Protective effects of ginseng on neurological disorders - Ong, Wei-Yi; Farooqui, Tahira; Koh, Hwee-Ling; Farooqui, Akhlaq A.; Ling, Eng-Ang (Frontiers in Aging Neuroscience, 2015)
Ginseng (Order: Apiales, Family: Araliaceae, Genus: Panax) has been used as a traditional herbal medicine for over 2000 years, and is recorded to have antianxiety, antidepressant and cognition enhancing properties. The protective effect of ginseng on neurological disorders is discussed in this review. Ginseng species and ginsenosides, and their intestinal metabolism and bioavailability are briefly introduced. This is followed by molecular mechanisms of effects of ginseng on the brain, including glutamatergic transmission, monoamine transmission, estrogen signaling, nitric oxide production, the Keap1/Nrf2 adaptive cellular stress pathway, neuronal survival, apoptosis, neural stem cells and neuroregeneration, microglia, astrocytes, oligodendrocytes and cerebral microvessels. The molecular mechanisms of the neuroprotective effects of ginseng in Alzheimer’s disease including Aβ formation, tau hyperphosphorylation and oxidative stress, major depression, stroke, Parkinson’s disease and multiple sclerosis / experimental allergic encephalitis are then presented. It is hoped that this discussion will stimulate more studies on the use of ginseng in these disorders.